Capsular polypyrrole hollow nanofibers: an efficient recyclable adsorbent for hexavalent chromium removal1. Issue 29 (7th August 2015) - Zhao, Jian; Li, Zhenyu; Wang, Jinfeng; Li, Quanxiang; Wang, Xungai
<x xml:space="preserve">Abstract</x> Capsular PPy-HNFs fabricated via in situ polymerization on organic templates showed an exceptional Cr(vi) adsorption capacity, up to 839.3 mg g−1.